(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Complementary split ring resonators (CSRR) (planar structures hence easily realizable nature) exhibit negative permittivity. The Design of a Novel Dual band Patch Antenna using CSRR and fractal concept is presented in this paper. The Kotch fractals are effectively implemented; circular, triangular slots are also further etched on the patch. The antennas radiating feature is improved by loading its ground plane with an innovative material named Metamaterial (Complementary Split Ring Resonator) Confirming an Omnidirectional pattern with radiating efficiency greater than 99, 86% respectively in the bands of its resonances. The model yields adequate Gain, Directivity at its resonances. The Key antenna parameter analysis (with the aid of commercial E.M simulator) carried out is also presented. Keywords: Microstrip Patch Antenna, Linear Polarization, Wireless Applications, Fractal, Koch, CSRR.